Improved Fibrinolysis after one Year of Treatment with Enalapril in Men and Women with Uncomplicated Myocardial Infarction - Boman, Kurt O. A.; Jansson, Jan-Håkan; Nyhlén, Katarina A.; Nilsson, Torbjörn K. (Thrombosis and Haemostasis, 2002)
To study long-term effects of enalapril on mass concentrations of tissue plasminogen activator (tPA), plasminogen activator inhibitor (PAI-1), tPA/PAI-1-complex and von Willebrand factor (vWF) in both genders with uncomplicated myocardial infarction.More than three months after an uncomplicated myocardial infarction 82 survivors (46 males, 36 females) were randomised to enalapril/placebo. PAI-1, tPA, tPA/PAI-1-complex and vWF were measured after two weeks, six and 12 months following randomisation. PAI-1 decreased significantly in both genders in the enalapril-treated group after two weeks, with a maximum decrease at six months (mean reduction: 31% equal to 9.8 µg X L–1, CI: 5.2 to 14.5 µg X L–1, p = 0.0001) and remained significantly lower at 12 months. Mass concentration of tPA decreased significantly (mean reduction; 1.81 µg X L–1, CI: 0.903 to 2.708 µg X L–1, p <0.001) after two weeks treatment in both genders but returned to baseline values at 12 months. The tPA/PAI-1-complex decreased and was significantly lower (mean reduction 0.96 µg X L–1, CI: 0.36 to 1.56 µg X L–1, p = 0.003) in the enalapril group after two weeks and six months (p = 0.037). No decrease of vWF was seen in the enalapril group.Enalapril treatment up to one year depressed mass concentrations of PAI-1 and transiently tPA and tPA/PAI-1 complex indicating an improvement of the fibrinolytic balance in both genders with uncomplicated myocardial infarction.
Keywords: Fibrinolysis; tissue plasminogen activator; plasminogen activator inhibitor; myocardial infarction; ACE-inhibitor